Anti-fatigue self-repairing material with high-energy biomimetic structure and preparation method thereof

CN121270976BActive Publication Date: 2026-11-03NANJING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410897571.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2026-11-03
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

Existing flexible materials are easily damaged during individual combat operations due to friction, collision, repeated bending/stretching/folding, etc., leading to unstable signals, equipment failure, and insufficient fatigue resistance, which limits their lifespan and performance in military applications.

Method used

A continuous high-energy biomimetic structure was constructed by blending waterborne polyurethane emulsion with phytic acid and inorganic filler MXene. The fatigue-resistant self-healing material was prepared by casting. Phytic acid was used as a crosslinking agent to implant the MXene skeleton into the waterborne polyurethane matrix.

Benefits of technology

It significantly improves the fatigue threshold and modulus of the material, while endowing the material with excellent thermal conductivity and infrared self-healing ability, extending the service life of flexible equipment and improving self-healing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121270976B_ABST
    Figure CN121270976B_ABST
Patent Text Reader

Abstract

The application discloses an anti-fatigue self-repairing material with high-energy bionic structure and a preparation method thereof. The method utilizes 5-(2-hydroxyethyl)-6-methyl-2-amino uracil, hydroxyl-terminated polycaprolactone diol, 2,2-dimethylol butyric acid and dicyclohexylmethane-4,4'-diisocyanate to copolymerize into a polyurethane elastomer under the catalysis of dibutyl tin dilaurate, then triethylamine is added to neutralize the butyric acid, water is added to emulsify to obtain a water-based polyurethane emulsion, finally, the water-based polyurethane emulsion is blended with a phytic acid and MXene aqueous solution to be cast into a film in a mode of film casting to obtain the anti-fatigue self-repairing material with the high-energy bionic structure. The anti-fatigue self-repairing material with the high-energy bionic structure has excellent fatigue threshold and modulus, and simultaneously has excellent heat conduction efficiency and infrared light response self-repairing capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials and relates to a fatigue-resistant self-healing material with a high-energy biomimetic structure and its preparation method. Background Technology

[0002] As modern warfare evolves towards informatization, intelligence, and unmanned operation, the demand for lightweight, intelligent, comfortable, and multifunctional integrated individual combat equipment is urgent. Compared to traditional bulky rigid materials, flexible materials have unique advantages in applications such as electronics, information, and energy. Their deformable and lightweight characteristics perfectly meet the design requirements of flexible electronic devices in modern individual combat systems. Currently, researchers have successfully developed a series of flexible intelligent equipment based on flexible materials, including wearable flexible electronic skin, integrated flexible batteries / capacitors, and flexible artificial muscles. These innovative research findings have extremely important applications in the military field. For example, flexible electronic skin, as a flexible and stretchable tactile sensing system that simulates the sensing function of biological skin, can not only provide tactile feedback to soldiers whose tactile senses are impaired due to burns or scalds during combat, but also collect signals such as soldiers' pulse, respiration, movement posture, and voice, enabling real-time monitoring of soldiers' health. Flexible artificial muscle actuators can replace traditional gear transmission devices, giving small combat robots carried by soldiers more flexible limbs. At the same time, flexible artificial muscle actuation systems can convert 70% of chemical energy into mechanical energy, with an efficiency far exceeding that of electric motors. Therefore, high-performance flexible materials are of great significance in the defense and military field.

[0003] However, it cannot be ignored that during individual combat operations, friction, collisions, and repeated bending / stretching / folding can impact flexible materials, causing damage such as scratches, cracks, and notches. This can lead to signal instability, inaccurate data, equipment malfunctions, and even functional loss in integrated flexible electronic devices, significantly weakening the soldier's individual combat capabilities. In summary, mechanical damage leading to the destruction of flexible materials is a major reason limiting the military application of flexible electronic devices and a problem that must be solved. Therefore, mimicking the "damage-sensing-self-healing" function of biological systems and developing flexible materials with self-repairing capabilities is crucial for extending the service life of flexible electronic devices. Furthermore, flexible electronic devices based on flexible materials will undergo thousands or even tens of thousands of cyclic strain loading processes during long-term use. If the fatigue resistance of the flexible material is poor, stress concentration can easily occur when microcracks appear and cyclic strain loading occurs, causing the flexible electronic device to tear rapidly before it can self-repair. For example, Canhui Lu et al. prepared a sensor with excellent conductivity by blending serine-modified MXene with waterborne polyurethane, but its fatigue resistance was relatively poor (ACS Nano., 2020, 14, 3, 2788–2797). In addition, Ting Zhang et al. prepared a flexible sensor with excellent mechanical properties by blending phytic acid (TA)-modified MXene with waterborne polyurethane, but the fatigue resistance of this sensor was still not ideal (Adv. Mater., 2023, 35, 35, 202302847). In contrast, self-healing flexible materials with excellent fatigue resistance can delay or even inhibit the propagation of microcracks, ensuring sufficient time for self-repair. Therefore, while endowing flexible materials with efficient self-healing properties, efforts should be made to improve their fatigue resistance and reveal the underlying mechanisms, which is of great scientific significance for the military applications of flexible materials. Summary of the Invention

[0004] The purpose of this invention is to provide a fatigue-resistant self-healing material with a high-energy biomimetic structure and its preparation method.

[0005] The technical solution for achieving the objective of this invention is as follows:

[0006] A method for preparing fatigue-resistant self-healing materials with high-energy biomimetic structures involves blending aqueous polyurethane emulsion with phytic acid (TA) and inorganic filler MXene, followed by casting. The specific steps are as follows:

[0007] Step 1: The hydroxyl-terminated polycaprolactone diol (HO-PCL-OH) is mixed with 2,2-dimethylolbutyric acid (DMBA), 5-(2-hydroxyethyl)-6-methyl-2-aminouracil (MIC), dicyclohexane-4,4'-diisocyanate (HMDI) in a molar ratio of 2:1.5:0.5:4.2. The hydroxyl-terminated polycaprolactone diol is mixed with 2,2-dimethylolbutyric acid, 5-(2-hydroxyethyl)-6-methyl-2-aminouracil, dicyclohexane-4,4'-diisocyanate and dibutyltin dilaurate catalyst in N,N-dimethylformamide. The mixture is stirred and refluxed at 70-80°C under a N2 atmosphere to obtain a polyurethane elastomer solution.

[0008] Step 2: Add triethylamine in an amount equal to DMBA to the polyurethane elastomer solution and reflux at 50-60°C. After the reaction is complete, add water to emulsify and dialyze to remove acetone and N,N-dimethylformamide to obtain an aqueous polyurethane emulsion.

[0009] Step 3: The phytic acid, inorganic filler two-dimensional carbonitride (MXene), and waterborne polyurethane are mixed in a mass ratio of 1:20:400. The mixture is stirred until homogeneous, then cast into a film and dried to obtain a fatigue-resistant self-healing material with a high-energy biomimetic structure.

[0010] Preferably, in step 1, the reflux reaction time is 30 hours or more.

[0011] Preferably, in step 2, the reflux reaction time is 5 minutes or more.

[0012] Preferably, in step 3, the mass ratio of phytic acid, MXene, and waterborne polyurethane is 0.15:3:50.

[0013] Preferably, in step 3, the blending time of phytic acid, MXene and waterborne polyurethane is more than 10 hours.

[0014] Preferably, in step 3, the drying temperature is 35-50℃ and the drying time is 24 hours or more.

[0015] The present invention also provides a fatigue-resistant self-healing material with a high-energy biomimetic structure prepared by the above preparation method.

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] This invention uses phytic acid as a crosslinking agent and MXene as a framework to implant into an aqueous polyurethane matrix, successfully constructing a continuous high-energy biomimetic structure in the material. The high-energy biomimetic structure constructed in this invention also improves the material's fatigue threshold (8101 Jm). -2This invention presents a contradictory mechanical property: high energy density and high modulus (40 MPa). Simultaneously, the high-energy biomimetic structure constructed in this invention endows the material with excellent thermal conductivity and self-healing capabilities in response to infrared light. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the high-energy biomimetic structure in the fatigue-resistant self-healing material with a high-energy biomimetic structure prepared in Example 1.

[0019] Figure 2 Tensile mechanical curves of the fatigue-resistant self-healing material with a high-energy biomimetic structure prepared in Example 1, the material with a general biomimetic structure prepared in Comparative Example 1, the waterborne polyurethane prepared in Comparative Example 2, and the self-healing material without a high-energy biomimetic structure prepared in Comparative Example 3.

[0020] Figure 3 The fatigue threshold statistics of the fatigue-resistant self-healing material with high-energy biomimetic structure prepared in Example 1, the material with general biomimetic structure prepared in Comparative Example 1, the waterborne polyurethane prepared in Comparative Example 2, and the self-healing material without high-energy biomimetic structure prepared in Comparative Example 3 are shown.

[0021] Figure 4 The mechanical repair curve of the fatigue-resistant self-healing material with a high-energy biomimetic structure prepared in Example 1;

[0022] Figure 5 The infrared light response heating and cooling curves of the fatigue-resistant self-healing material with a high-energy biomimetic structure prepared in Example 1 and the material with a general biomimetic structure prepared in Comparative Example 1 are shown. Detailed Implementation

[0023] The present invention will now be described in further detail with reference to the embodiments and accompanying drawings.

[0024] In the following examples, 5-(2-hydroxyethyl)-6-methyl-2-aminouracil was prepared according to reference [J. Am. Chem. Soc., 2018, 140, 5280], and the specific steps were as follows:

[0025] Weigh 5.12 g of 2-acetylbutyrolactone, 11 mL of triethylamine, and 3.60 g of guanidine carbonate. Recycle the mixture in 40 mL of ethanol under stirring and reflux at 60 °C for 4 hours. After the reaction, filter the mixture through suction to obtain a yellow powder solid. Wash the powder further with ethanol and place the product in a 60 °C oven for 12 hours to obtain a white 5-(2-hydroxyethyl)-6-methyl-2-aminouracil powder.

[0026] Example 1

[0027] 0.0845 g of 5-(2-hydroxyethyl)-6-methyl-2-aminouracil powder, 4 g of hydroxyl-terminated polycaprolactone diol, 0.222 g of 2,2-dimethylolbutyric acid, 1.10 g of dicyclohexane-4,4'-diisocyanate, and 0.1 mL of dibutyltin dilaurate were placed in a three-necked flask containing 2 mL of N,N-dimethylformamide solvent. The mixture was refluxed at 70 °C for 30 hours. After the solution cooled to 60 °C, triethylamine was added to the flask in an equimolar ratio with 2,2-dimethylolbutyric acid. The mixture was then refluxed at 60 °C for another 10 minutes. After the reaction was completed, 10 mL of distilled water was added to the container for emulsification. After emulsification for 30 minutes, the N,N-dimethylformamide was removed using a dialysis bag to obtain an aqueous polyurethane emulsion. Finally, phytic acid (0.01g), 5mL MXene aqueous solution (solid content 0.2g) and waterborne polyurethane emulsion (solid content 4g) were mixed and stirred for 12 hours. Then, the mixture was cast into a film and dried in an oven at 45℃ for 24 hours to obtain a fatigue-resistant self-healing material with a high-energy biomimetic structure.

[0028] Comparative Example 1

[0029] This comparative example is largely the same as Example 1, except that phytic acid is not added, resulting in a material with a general biomimetic structure.

[0030] Comparative Example 2

[0031] 0.0845 g of 5-(2-hydroxyethyl)-6-methyl-2-aminouracil powder, 4 g of hydroxyl-terminated polycaprolactone diol, 0.222 g of 2,2-dimethylolbutyric acid, 1.10 g of dicyclohexane-4,4'-diisocyanate, and 0.1 mL of dibutyltin dilaurate were placed in a three-necked flask containing 2 mL of N,N-dimethylformamide solvent. The mixture was refluxed at 70 °C for 30 hours. After the solution cooled to 60 °C, triethylamine in an equimolar ratio with 2,2-dimethylolbutyric acid was added to the flask. The mixture was then refluxed at 60 °C for another 10 minutes. The mixture was then cast into a film and dried in an oven at 45 °C for 24 hours to obtain the waterborne polyurethane material.

[0032] Comparative Example 3

[0033] 0.0845 g of 5-(2-hydroxyethyl)-6-methyl-2-aminouracil powder, 4 g of hydroxyl-terminated polycaprolactone diol, 0.222 g of 2,2-dimethylolbutyric acid, 1.10 g of dicyclohexane-4,4'-diisocyanate, and 0.1 mL of dibutyltin dilaurate were placed in a three-necked flask containing 2 mL of N,N-dimethylformamide solvent. The mixture was refluxed at 70 °C for 30 hours. After the solution cooled to 60 °C, triethylamine was added to the flask in an equimolar ratio with 2,2-dimethylolbutyric acid. The mixture was then refluxed at 60 °C for another 10 minutes. Finally, 0.01 g of phytic acid and 5 mL of N,N-dimethylformamide were added to the flask. MXene aqueous solution (solid content 0.2g) was mixed with aqueous polyurethane emulsion (solid content 4g), and stirred for 12 hours. The mixture was then cast into a film and dried in an oven at 45℃ for 24 hours to obtain a self-healing material without a high-energy biomimetic structure.

[0034] Figure 1 The diagram shows the high-energy biomimetic structure in the fatigue-resistant self-healing material with a high-energy biomimetic structure prepared in Example 1. It can be seen that there is a continuous high-energy biomimetic structure constructed from MXene in the waterborne polyurethane matrix.

[0035] Figure 2 The tensile mechanical curves of the fatigue-resistant self-healing material with a high-energy biomimetic structure prepared in Example 1, the material with a general biomimetic structure prepared in Comparative Example 1, the waterborne polyurethane prepared in Comparative Example 2, and the self-healing material without a high-energy biomimetic structure prepared in Comparative Example 3 show that the fatigue-resistant self-healing material with the high-energy biomimetic structure has the best mechanical strength (45 MPa), modulus (40 MPa), and elongation (2450%). This demonstrates that the high-energy biomimetic structure can comprehensively improve the basic mechanical properties of the material.

[0036] Figure 3 The fatigue threshold statistics of the fatigue-resistant self-healing material with a high-energy biomimetic structure prepared in Example 1, the material with a general biomimetic structure prepared in Comparative Example 1, the waterborne polyurethane prepared in Comparative Example 2, and the self-healing material without a high-energy biomimetic structure prepared in Comparative Example 3 are shown in the figure. It can be seen that the fatigue-resistant self-healing material with a high-energy biomimetic structure has the highest fatigue threshold, reaching 8101 J / m. -2 This demonstrates that the high-energy biomimetic structure can improve the fatigue threshold of materials.

[0037] Figure 4 The mechanical repair curve of the fatigue-resistant self-healing material with a high-energy biomimetic structure prepared in Example 1 shows that the fatigue-resistant self-healing material with a high-energy biomimetic structure has excellent self-healing ability, and its mechanical properties can be almost completely repaired.

[0038] Figure 5The infrared light response heating and cooling curves of the fatigue-resistant self-healing material with a high-energy biomimetic structure prepared in Example 1 and the material with a general biomimetic structure prepared in Comparative Example 1 show that the fatigue-resistant self-healing material with a high-energy biomimetic structure has a faster heating and cooling rate, which indicates that the high-energy biomimetic structure can improve the thermal conductivity of the material.

Claims

1. A method for preparing a fatigue-resistant self-healing material with a high-energy biomimetic structure, characterized in that, The specific steps are as follows: Step 1: The hydroxyl-terminated polycaprolactone diol, 2,2-dimethylolbutyric acid, 5-(2-hydroxyethyl)-6-methyl-2-aminouracil, dicyclohexane-4,4'-diisocyanate, and catalyst dibutyltin dilaurate are mixed in N,N-dimethylformamide and stirred under N2 atmosphere at 70-80°C to obtain a polyurethane elastomer solution. Step 2: Add triethylamine in an amount equal to 2,2-dimethylolbutyric acid to the polyurethane elastomer solution, reflux at 50-60°C, emulsify with water after the reaction, and remove N,N-dimethylformamide by dialysis to obtain an aqueous polyurethane emulsion. Step 3: Mix the aqueous solutions of phytic acid and MXene with the aqueous polyurethane emulsion at a mass ratio of 1:20:400, stir until uniformly mixed, then cast into a film and dry to obtain a fatigue-resistant self-healing material with a high-energy biomimetic structure.

2. The preparation method according to claim 1, characterized in that, In step 1, the reflux reaction time is more than 30 hours.

3. The preparation method according to claim 1, characterized in that, In step 2, the reflux reaction time is more than 5 minutes.

4. The preparation method according to claim 1, characterized in that, In step 3, the blending time of phytic acid, MXene aqueous solution and waterborne polyurethane emulsion is more than 10 hours.

5. The preparation method according to claim 1, characterized in that, In step 3, the drying temperature is 35~50℃ and the drying time is more than 24 hours.

6. The fatigue-resistant self-healing material with a high-energy biomimetic structure prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Reinforcing and toughening self-repairing material with dragonfly wing microstructure and preparation method of reinforcing and toughening self-repairing material

    CN114426775A

  • Antibacterial and self-repairing composite coating based on visible light induction MXene / waterborne polyurethane and preparation method of antibacterial and self-repairing composite coating

    CN116694219A